Implementasi Euthanasia dalam Perspektif Ulama dan Hak Asasi Manusia - Warjiyati, Sri (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
Euthanasia is a problematical issue among doctors, legal practitioners, and religious scholars. It has become a topic of discussion in various countries, especially Indonesia and Malaysia when viewed from the perspective of religion and human rights. The scholars agree that an action can only be classified as a Jarimah if the action is strictly prohibited by syara'. Although there is no clarity or certainty in determining whether euthanasia is a crime or not, the concept of euthanasia itself, formulated by experts, is written and is prohibited in the Al-Quran and Hadith. For example in the Al-Qur'an in QS. Al-An'am verse 151: "And do not kill the soul that Allah has haraam (kills it) but with the right cause". Killing here means killing in any way, including killing with the help of others, such as the concept of active euthanasia. Meanwhile, from a human rights perspective, euthanasia is an effort to eliminate the right to life of a human being, because the nature of euthanasia itself eliminates human life because it will harm others.